2018
DOI: 10.15343/0104-7809.20184204811822
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and reduction of hours of sleep: results from cross-sectional study

Abstract: Childhood obesity is a prevalent condition in modern societies which can negatively impact people's health during life. Although there are several factors contributing to obesity, sleep duration has been pointed out as an important risk factor. This study, held in the district of Porto, Portugal, aimed to analyze the association between sleep duration and the nutritional status of school-aged children studying in Portugal. 1396 students from 35 and 3 public and private schools, respectively, were contacted, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…On average, sleeping less than 10-9 hours was associated with overweight/obesity or a higher incidence of obesity was found in short-sleepers. 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, sleeping less than 10-9 hours was associated with overweight/obesity or a higher incidence of obesity was found in short-sleepers. 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Resultsmentioning
confidence: 99%
“…13 The studies of Guo et al 23 and Durán et al 25 had the lowest score in the quality analysis, and were considered poor, with six positive answers (in a total of 14) in the NIH tool. Most of the studies were considered fair and had between seven and nine positive answers in the NIH tool (King et al, 7 Kordas et al, 34 Christoph et al, 27 Katsa et al, 22 Carrillo-Larco et al, 16 Kordas et al, 35 Jiang et al, 21 Jong et al, 26 Hitze et al, 31 Chamorro et al, 15 Ruotolo et al, 33 Cicek et al, 20 Agüero et al, 19 Durán et al, 25 Corso et al, 24 Bazán et al, 18 Marques et al, 6 Aravena et al, 28 Giovaninni et al 29 ), and the highest quality studies were the ones made by Agüero and Riveira, 17 Golley et al 30 and Na et al, 32 with ten positive answers. The compliance with the STROBE checklist showed that only three studies fulfilled more than 75% (Agüero et al, 19 Chamorro et al 15 and King et al 7 ) of the items of the checklist, and the others accomplished between 43.7 and 71.8%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em média, dormir menos de 10-9 horas foi associado com sobrepeso/obesidade, ou maior incidência de obesidade foi verificada em pessoas com sono de curta duração. 6,[15][16][17][18][19][20][21][22][23][24][25][26] Em estudo transversal realizado com 1.810 crianças de 6 a 11 anos, a qualidade do sono foi avaliada pelo questionário Pittsburgh Sleep Quality Index (PSQI), e 49,9% das crianças avaliadas dormiam menos do que o recomendado (<10 horas por dia), sendo que essa restrição de sono foi maior durante a semana e Figura 1 Fluxograma de seleção de estudos. Analisar a associação entre duração do sono e estado nutricional de crianças em idade escolar de Portugal; 829 alunos; ±9 anos.…”
Section: Métodounclassified
“…Como consequência da fadiga causada pela perda de sono, observa-se menor gasto energético durante o dia, o que leva a um comportamento sedentário. 6 Assim, maior ingestão energética e de alimentos palatáveis, como açúcar e alimentos ricos em gordura, são uma resposta ao débito de sono. 7 Em adultos, a restrição de sono foi associada a mudanças nos reguladores hormonais do balanço energético, como aumento de grelina e diminuição da secreção de leptina.…”
Section: Introductionunclassified